A paper coated with a bird nest-rice leaf composite structure fluorine-free high-strength multifunctional super-hydrophobic coating and a preparation method thereof
Patent Information
- Application Number
- CN202611325330.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]针对现有技术中存在的问题,本发明提供一种涂覆有仿鸟巢-水稻叶复合结构无氟高强度多功能超疏水涂层纸张及其制备方法,从而解决现有超疏水涂层技术普遍面临含氟材料环境毒性高、纳米填料结构不稳定以及仿生设计缺乏有效力学支撑,导致涂层在环保性、耐久性和机械强度上难以兼顾的技术问题
本发明公开一种涂覆有仿鸟巢-水稻叶复合结构无氟高强度多功能超疏水涂层纸张的制备方法,该方法通过仿鸟巢-水稻叶复合结构设计与全绿色原料体系,解决了现有超疏水涂层在环保性、耐久性和机械强度上难以兼顾的难题。首先,在环保性方面,该方法完全摒弃了有毒的含氟化合物,转而采用聚二甲基硅氧烷、纤维素纳米纤维、二氧化硅及天然蜡等环境友好型材料,从源头上确保了涂层的绿色无毒特性。其次,针对机械强度与耐久性问题,该方法的核心在于仿生复合结构设计:通过喷涂硅烷偶联剂改性的纤维素纳米纤维,在纸张表面构建了一个仿鸟巢的三维网络骨架,这一结构为涂层提供了连续且柔性的力学支撑,显著提升了涂层的整体强度和抗变形能力;在此基础上,再负载二氧化硅纳米粒子以构建纳米级粗糙度,并模仿水稻叶表面,用天然蜡进行低表面能修饰,最终形成一个集力学骨架与疏水表层于一体的稳固复合结构。这种设计不仅通过化学改性和物理互锁增强了各组分与纸基的结合力,还有效防止了表面微结构在摩擦或刮擦中脱落,从而赋予了涂层优异的机械耐久性。综上,该方法通过材料选择与结构创新的双重策略,成功制备出一种兼具环保、高强、耐久和超疏水性能的多功能涂层。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of paper and coating technology, and relates to a fluorine-free, high-strength, multifunctional superhydrophobic paper coated with a bird's nest-rice leaf composite structure and its preparation method. Background Technology
[0002] Paper, as a fundamental material, plays an indispensable role in many fields such as food packaging, calligraphy and painting creation, and cultural relic collection. It is not only a necessity in people's daily lives but also a key medium for inheriting historical civilization, possessing enormous potential for industrial production and cultural relic protection. However, paper is mainly composed of cellulose, hemicellulose, and lignin. Its core components, cellulose and hemicellulose, naturally possess strong hydrophilicity, making paper highly susceptible to moisture, deformation, brittleness, crumbling, and acidification. For ancient paper artifacts, the deterioration and damage caused by moisture during long-term storage are further exacerbated. Therefore, addressing the practical needs of paper processing, long-term protection of cultural relics, and storage preservation, hydrophobic modification of paper to prevent moisture penetration into the fiber interior, improve its mechanical durability, and delay mechanical degradation caused by aging is particularly urgent.
[0003] Constructing superhydrophobic coatings requires meeting two core conditions simultaneously: low surface energy chemical composition and hierarchical micro / nano roughened structures. In terms of low surface energy modification materials, fluorinated compounds (such as perfluorinated and polyfluoroalkyl compounds) are widely used due to their extremely low surface energy. For constructing roughened morphologies, nanofillers are commonly employed. Diverse biological structures in nature, such as rice leaves with typical superhydrophobic surfaces and bird nests with their interlaced branches forming a mechanical support network, provide excellent biomimetic prototypes for regulating wetting interfaces. Existing research also attempts to draw inspiration from these biological structures to achieve superhydrophobic effects by constructing micro / nano roughened surfaces.
[0004] However, existing technologies still have significant problems. On the one hand, fluorinated compounds have extremely poor biodegradability and can continuously harm human health and ecosystems, leading to restrictions on their use in several industries. On the other hand, nanofillers used to construct rough morphologies generally suffer from poor dispersibility, insufficient adhesion to paper substrates, and easy wear and failure of surface microstructures, significantly shortening the coating's lifespan. Furthermore, existing biomimetic superhydrophobic modification strategies generally only construct micro-nano rough surfaces, lacking a continuous mechanical support framework, resulting in weak overall mechanical strength and durability. In conclusion, developing a green, low-toxicity, structurally stable coating preparation scheme that combines excellent superhydrophobic properties, mechanical durability, and mechanical properties is of great practical necessity and significant research importance. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides a paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure and its preparation method. This solves the technical problems that existing superhydrophobic coating technologies generally face, such as the high environmental toxicity of fluorine-containing materials, the instability of nanofiller structures, and the lack of effective mechanical support for biomimetic designs, which makes it difficult to balance environmental friendliness, durability, and mechanical strength.
[0006] This invention is achieved through the following technical solution: A method for preparing paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating featuring a bird's nest-rice leaf composite structure includes the following steps: S1: After mixing polydimethylsiloxane, curing agent and tetrahydrofuran evenly, spray it onto the paper surface and perform a room temperature pre-curing to obtain polydimethylsiloxane coated paper. S2: After uniformly mixing silane coupling agent modified cellulose nanofibers with anhydrous ethanol, the mixture is sprayed onto the surface of the polydimethylsiloxane coated paper and pre-cured at room temperature for a second time to obtain paper coated with a bird's nest-like structure intermediate layer. S3: After uniformly mixing silica nanoparticles with tetrahydrofuran, spray the mixture onto the surface of the paper coated with the bird's nest structure intermediate layer, and perform three room temperature pre-curing processes to obtain silica-coated paper. S4: Dissolve the wax in anhydrous ethanol, heat at a constant temperature until the system is completely clear, then spray it onto the surface of silica-coated paper and cure at room temperature to obtain the paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure.
[0007] Optionally, the mass ratio of the polydimethylsiloxane, curing agent and tetrahydrofuran is 1:0.1:(5~20); the time for the first room temperature pre-curing is 2~4 h.
[0008] Optionally, the preparation process of the silane coupling agent modified cellulose nanofibers is as follows: the aqueous dispersion of cellulose nanofibers is mixed evenly with anhydrous ethanol, the pH of the system is adjusted to 4 with glacial acetic acid, and then the silane coupling agent is added dropwise. After constant temperature reaction, the silane coupling agent modified cellulose nanofibers are obtained; the silane coupling agent includes one of methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, n-hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, methyltriethoxysilane, and methyltriisopropoxysilane.
[0009] Optionally, the solid content of the cellulose nanofiber aqueous dispersion is 1%~5%; the mass ratio of the silane coupling agent to the cellulose nanofiber aqueous dispersion and anhydrous ethanol is (1~2):8; and the volume ratio of the cellulose nanofiber aqueous dispersion to anhydrous ethanol is 1:9.
[0010] Optionally, the mass ratio of the silane coupling agent-modified cellulose nanofibers to anhydrous ethanol is (0.0025~0.025):1; the secondary room temperature pre-curing time is 2~4 h.
[0011] Optionally, the mass ratio of silica nanoparticles to tetrahydrofuran is (0.0025~0.025):1, and the amount of silica nanoparticles added is equal to the content of silane coupling agent modified cellulose nanofibers; the time for the three room temperature pre-curing cycles is 2~4 h.
[0012] Optionally, the preparation process of the silica nanoparticles is as follows: tetraethyl orthosilicate, anhydrous ethanol and ammonia water are mixed in a volume ratio of 5:25:1, and the mixture is magnetically stirred at 500~1000 rpm at room temperature for 12~24 h. After the reaction is completed, the precipitate is separated by centrifugation at 8000~10000 rpm, and the precipitate is dried at 60~80℃ for 4~8 h.
[0013] Optionally, in step S4, 0.25~0.5 g of wax is dissolved in 20 g of anhydrous ethanol; the room temperature curing time is 24~48 h; the wax includes one of beeswax, carnauba wax, candle wax, rice bran wax and insect wax.
[0014] Optionally, the spraying process in steps S1 to S4 is as follows: spray gun nozzle diameter 0.5 mm, spraying distance 10 to 20 cm, spraying pressure 0.2 MPa; each layer is sprayed 3 times, and the single spraying time is 3 s.
[0015] A type of paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating featuring a bird's nest-rice leaf composite structure is prepared by the method described above.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a method for preparing paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating featuring a bird's nest-rice leaf composite structure. This method, through its bird's nest-rice leaf composite structure design and entirely green raw material system, solves the problem of existing superhydrophobic coatings struggling to balance environmental friendliness, durability, and mechanical strength. Firstly, regarding environmental friendliness, this method completely eliminates toxic fluorine-containing compounds, instead employing environmentally friendly materials such as polydimethylsiloxane, cellulose nanofibers, silica, and natural waxes, ensuring the coating's green and non-toxic properties from the source. Secondly, regarding the issues of mechanical strength and durability, the core of this method lies in the biomimetic composite structure design: by spraying cellulose nanofibers modified with silane coupling agent, a three-dimensional network skeleton resembling a bird's nest is constructed on the paper surface. This structure provides continuous and flexible mechanical support for the coating, significantly improving its overall strength and resistance to deformation. Based on this, silica nanoparticles are then loaded to create nanoscale roughness, and mimicking the surface of rice leaves, a low surface energy modification with natural wax is applied, ultimately forming a stable composite structure integrating a mechanical skeleton and a hydrophobic surface. This design not only enhances the bonding force between the components and the paper substrate through chemical modification and physical interlocking, but also effectively prevents the surface microstructure from detaching during friction or scratching, thus endowing the coating with excellent mechanical durability. In summary, this method, through a dual strategy of material selection and structural innovation, successfully prepares a multifunctional coating that combines environmental friendliness, high strength, durability, and superhydrophobicity.
[0017] Furthermore, the mass ratio of polydimethylsiloxane, curing agent, and tetrahydrofuran is 1:0.1:(5~20); the initial room temperature pre-curing time is 2~4 hours. By setting the mass ratio of polydimethylsiloxane, curing agent, and tetrahydrofuran to 1:0.1:(5~20) and controlling the pre-curing time to 2~4 hours, the viscosity and cross-linking degree of the underlying coating can be precisely controlled. This ensures that a base film with uniform thickness, strong adhesion, and moderate flexibility can be formed on the paper surface, providing a reliable "foundation" for the stable construction of subsequent functional layers and effectively enhancing the bonding force between the entire composite coating and the paper substrate.
[0018] Furthermore, the preparation process of the silane coupling agent modified cellulose nanofibers is as follows: Aqueous dispersions of cellulose nanofibers are mixed uniformly with anhydrous ethanol, the pH of the system is adjusted to 4 with glacial acetic acid, and then the silane coupling agent is added dropwise. After a constant-temperature reaction, the silane coupling agent modified cellulose nanofibers are obtained. Here, adjusting the pH to 4 with glacial acetic acid creates an optimal acidic environment for the hydrolysis and grafting reaction of the silane coupling agent, thereby ensuring that the silane coupling agent can be efficiently and stably grafted onto the surface of the cellulose nanofibers. This step is crucial for constructing the bird's nest-like mechanical framework. The modified cellulose nanofibers have reduced surface energy, better compatibility with the subsequent hydrophobic layer, and also possess stronger hydrophobic potential. Furthermore, the silane coupling agent includes one of methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, n-hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, methyltriethoxysilane, and methyltriisopropoxysilane. This selection avoids the biotoxicity problems of traditional fluorinated compounds, which are difficult to degrade and easily accumulate in the environment, ensuring the environmental friendliness of the coating. Simultaneously, these silane coupling agents can be efficiently grafted onto the surface of cellulose nanofibers, not only endowing them with hydrophobic properties but also providing a key chemical basis for constructing a bird's nest-like three-dimensional network framework, thus synergistically achieving both environmental friendliness and high performance in the coating.
[0019] Furthermore, the solid content of the cellulose nanofiber aqueous dispersion is 1%~5%; the mass ratio of the silane coupling agent to the cellulose nanofiber aqueous dispersion and anhydrous ethanol is (1~2):8. Here, the solid content of the cellulose nanofiber aqueous dispersion is controlled at 1%~5%, and the mass ratio of the silane coupling agent to the dispersion and ethanol is controlled at (1~2):8. In addition, the volume ratio of the cellulose nanofiber aqueous dispersion to anhydrous ethanol is 1:9. By precisely controlling the concentration of cellulose nanofibers and the proportion of the modifier, it is possible to ensure that the silane coupling agent is efficiently and stably grafted onto the fiber surface, while ensuring that the modified cellulose nanofibers have good dispersibility in the solvent and avoiding agglomeration. This lays the foundation for the subsequent spraying to form a stable and mechanically excellent bird's nest-like three-dimensional network skeleton, thereby significantly improving the overall strength and durability of the coating.
[0020] Furthermore, the mass ratio of the silane coupling agent-modified cellulose nanofibers to anhydrous ethanol is (0.0025~0.025):1; the secondary room temperature pre-curing time is 2~4 h. Controlling the mass ratio of the silane coupling agent-modified cellulose nanofibers to anhydrous ethanol at (0.0025~0.025):1 and pre-curing for 2~4 hours allows for precise control of the density and thickness of the intermediate layer network. Appropriate concentration and curing time ensure that the cellulose nanofibers are uniformly spread on the adhesion substrate, forming a continuous and complete bird's nest-like three-dimensional network through physical entanglement, providing core mechanical support for the entire coating, while avoiding the impact of excessive coating thickness on the paper's flexibility and breathability.
[0021] Furthermore, the mass ratio of silica nanoparticles to tetrahydrofuran is (0.0025~0.025):1, and the amount of silica nanoparticles added is equal to the content of silane coupling agent modified cellulose nanofibers; the three room temperature pre-curing times are 2~4 h, where the mass ratio of silica nanoparticles to tetrahydrofuran is controlled at (0.0025~0.025):1, and the amount added is equal to the content of modified cellulose nanofibers, while pre-curing for 2~4 hours. This design ensures that rigid silica nanoparticles can be uniformly loaded onto the flexible cellulose nanofiber network, which not only enhances the strength of the network nodes but also constructs an ideal micro / nano second-order rough structure, which is the key physical basis for achieving superhydrophobicity.
[0022] Furthermore, the preparation process of the silica nanoparticles is as follows: tetraethyl orthosilicate, anhydrous ethanol, and ammonia are mixed at a volume ratio of 5:25:1, and the mixture is magnetically stirred at 500-1000 rpm for 12-24 h at room temperature. After the reaction, the precipitate is separated by centrifugation at 8000-10000 rpm, and the precipitate is dried at 60-80℃ for 4-8 h. By using the sol-gel method and controlling the stirring speed, reaction time, and drying conditions, spherical silica nanoparticles with uniform particle size and good dispersibility can be prepared. High-quality nanoparticles are a prerequisite for constructing a uniform and stable micro-nano rough structure, and directly determine the stability and reproducibility of the superhydrophobic properties of the final coating.
[0023] Furthermore, in step S4, 0.25~0.5 g of wax is dissolved in 20 g of anhydrous ethanol; the room temperature curing time is 24~48 h. This concentration range ensures that after spraying, the wax solution uniformly covers the surface of silica nanoparticles through the thermal response phase change effect, effectively reducing the surface energy of the entire coating and endowing it with superhydrophobic properties. Sufficient curing time ensures that the wax layer can fully crystallize and firmly bond with the underlying structure, forming a dense, continuous, and durable hydrophobic barrier. In addition, the wax includes one of beeswax, carnauba wax, candle wax, rice bran wax, and insect wax. These waxes are all natural waxes. Natural waxes not only endow the coating with extremely low surface energy to achieve superhydrophobicity, but their excellent biocompatibility and biodegradability also further enhance the environmental friendliness of the product, meeting the requirements of sustainable development.
[0024] Furthermore, the spraying process in steps S1-S4 is as follows: spray gun nozzle diameter 0.5 mm, spraying distance 10-20 cm, spraying pressure 0.2 MPa; each layer is sprayed 3 times, with a single spraying time of 3 seconds. By fixing the spray gun nozzle diameter, spraying distance, pressure, and the number of sprays and time, the coating preparation process is standardized and controllable. This simple and repeatable spraying process not only has a low operating threshold but is also very conducive to large-area, large-scale production, ensuring the uniformity of coating thickness and the consistency of performance, laying a solid technological foundation for the technology to move from the laboratory to industrial application. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 The image shows the surface morphology of the silica nanoparticles prepared in Example 1 of this invention. Figure 2 A surface morphology diagram of Xuan paper; Figure 3 This is a surface morphology image of Xuan paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure prepared in Example 1 of the present invention. Figure 4 The water contact angle of Xuan paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure obtained in Example 1 of this invention; Figure 5 The water contact angle of the original Xuan paper; Figure 6 A photograph of the original Xuan paper; Figure 7 A photograph of Xuan paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure, prepared in Example 1 of this invention. Figure 8 This is a surface morphology image of Xuan paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure, prepared in Example 2 of the present invention. Detailed Implementation
[0027] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0028] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0029] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0030] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0031] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0032] This invention provides a method for preparing paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating featuring a bird's nest-rice leaf composite structure, comprising the following steps: S1: After mixing polydimethylsiloxane, curing agent and tetrahydrofuran evenly, spray it onto the paper surface and perform a room temperature pre-curing to obtain polydimethylsiloxane coated paper. The mass ratio of polydimethylsiloxane, curing agent and tetrahydrofuran is 1:0.1:(5~20), and the time for one room temperature pre-curing is 2~4 h.
[0033] The paper is Xuan paper, printing paper, or kraft paper, with Xuan paper being preferred.
[0034] The curing agent is a curing agent used in conjunction with polydimethylsiloxane, such as Sylgard 184 curing agent (component B), which is used in combination with polydimethylsiloxane adhesive (component A).
[0035] S2: After uniformly mixing silane coupling agent modified cellulose nanofibers with anhydrous ethanol, the mixture is sprayed onto the surface of the polydimethylsiloxane coated paper and pre-cured at room temperature for a second time to obtain paper coated with a bird's nest-like structure intermediate layer. The preparation process of the silane coupling agent modified cellulose nanofibers is as follows: the aqueous dispersion of cellulose nanofibers (solid content of 1%~5%) and anhydrous ethanol are thoroughly mixed at a volume ratio of 1:9. The pH value of the system is adjusted to 4 with glacial acetic acid. Then, the silane coupling agent is added dropwise. The mass ratio of silane coupling agent to aqueous dispersion of cellulose nanofibers and anhydrous ethanol is (1~2):8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 8000~10000 rpm for 5 min, the silane coupling agent modified cellulose nanofibers are obtained by washing three times with anhydrous ethanol.
[0036] The silane coupling agent is fluorine-free and includes, but is not limited to, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, n-hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, methyltriethoxysilane, methyltriisopropoxysilane, etc.
[0037] The mass ratio of the silane coupling agent-modified cellulose nanofibers to anhydrous ethanol is (0.0025~0.025):1, and the secondary room temperature pre-curing time is 2~4 h.
[0038] S3: After uniformly mixing silica nanoparticles with tetrahydrofuran, spray the mixture onto the surface of the paper coated with the bird's nest structure intermediate layer, and perform three room temperature pre-curing processes to obtain silica-coated paper. The mass ratio of silica nanoparticles to tetrahydrofuran is (0.0025~0.025):1, and the amount of silica nanoparticles added is equal to the content of silane coupling agent modified cellulose nanofibers. The time for three room temperature pre-curing cycles is 2~4 h.
[0039] The preparation process of the silica nanoparticles is as follows: tetraethyl orthosilicate, anhydrous ethanol and ammonia water are mixed in a volume ratio of 5:25:1, and the mixture is magnetically stirred at 500~1000 rpm at room temperature for 12~24 h. After the reaction is completed, the precipitate is separated by centrifugation at 8000~10000 rpm, and the precipitate is dried at 60~80℃ for 4~8 h.
[0040] S4: Dissolve the wax in anhydrous ethanol, heat at a constant temperature until the system is completely clear, then spray it onto the surface of silica-coated paper and cure at room temperature to obtain the paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure.
[0041] The above process is as follows: 0.25~0.5 g of wax is dissolved in 20 g of anhydrous ethanol, and heated at a constant temperature for 30 min according to the melting point of the wax until the system is completely clear. Then, it is sprayed onto the surface of silica-coated paper and cured at room temperature to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating paper with a bird's nest-rice leaf composite structure.
[0042] The wax is a natural wax, including but not limited to beeswax, carnauba wax, candle wax, rice bran wax, etc., and the curing time at room temperature is 24~48 hours.
[0043] Preferably, the spraying process in steps S1 to S4 is as follows: spray gun nozzle diameter 0.5 mm, spraying distance 10 to 20 cm, spraying pressure 0.2 MPa; each layer is sprayed 3 times, and the single spraying time is 3 s.
[0044] In addition, the present invention discloses a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure prepared by the above method. The composite coating comprises, from the paper surface outward, the following layers in sequence: an adhesion bottom layer formed by pre-curing polydimethylsiloxane, an imitation bird's nest structure middle layer formed by cellulose nanofibers modified with silane coupling agent, and an imitation rice leaf structure top layer composed of silica nanoparticles and wax.
[0045] This invention discloses a method for preparing paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating featuring a bird's nest-rice leaf composite structure. Inspired by the excellent overall mechanical stability and deformation resistance of the bird's nest structure, and the natural superhydrophobic properties of rice leaves derived from the distribution of micron-sized papillary structures on their surface and the coating of nano-wax crystals, this method uses silane coupling agents to modify cellulose nanofibers to construct a three-dimensional mechanically interlocked framework resembling a bird's nest, and uses silica nanoparticles and wax to construct a low surface energy hydrophobic structure resembling rice leaf papillae. This method synergistically solves the technical problem in the prior art of achieving a balance between superhydrophobicity, transparency, mechanical durability, acid and alkali corrosion resistance, and paper-based mechanical strength.
[0046] The coated Xuan paper prepared using the method described in this invention exhibits superhydrophobicity (water contact angle greater than 150°), superior light transmittance compared to the original paper, and minimal color difference (ΔE less than 5), thus fully preserving the original color of the Xuan paper. A flexible three-dimensional network is constructed using silane coupling agent-modified cellulose nanofibers, while proportionally proportioned rigid silica nanoparticles enhance the network nodes and impart surface roughness. Simultaneously, an appropriate amount of wax utilizes the thermal response phase transition effect to fill network voids and physically weld connection points, forming a dense and continuous coating. This coating not only resists external impacts and deformation but also endows the system with low surface energy and lubrication properties. After mechanical durability tests such as friction and wear, tape peeling, and finger rubbing, as well as prolonged immersion in acids and alkalis, the coating maintains excellent hydrophobic properties. Furthermore, this coating significantly improves the tensile strength of the Xuan paper.
[0047] This invention uses a spraying method to prepare a composite coating with a bird's nest-rice leaf composite structure. The preparation process is simple, has a low operating threshold, can achieve large-scale preparation, has low preparation cost, and the raw materials are all natural materials that are non-toxic, harmless, and have good environmental compatibility, which is conducive to promoting the industrialization of superhydrophobic protective coatings.
[0048] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0049] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0050] Example 1 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 5% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 5 g of methyltrimethoxysilane dropwise. The mass ratio of methyltrimethoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 1:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 8000 rpm for 5 min, the silane coupling agent modified cellulose nanofiber is obtained after washing 3 times with anhydrous ethanol. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 500 rpm for 12 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 8000 rpm and dried at 80℃ for 6 h to prepare silica nanoparticles. 3) Mix polydimethylsiloxane, curing agent and tetrahydrofuran at a mass ratio of 1:0.1:10, and then spray it onto the surface of Xuan paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times. Each spraying time is 3 s. Pre-cur at room temperature for 2 h to obtain polydimethylsiloxane coated Xuan paper. 4) The silane coupling agent modified cellulose nanofibers prepared in step 1) are mixed with anhydrous ethanol at a mass ratio of 0.0025:1. The mixture is then sprayed onto the surface of the polydimethylsiloxane-coated Xuan paper obtained in step 3). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 2 h to obtain Xuan paper with an imitation bird's nest structure middle layer coating. 5) Mix the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.0025:1, and then spray the mixture onto the surface of the bird's nest structure intermediate layer coated paper obtained in step 4). Pre-cur at room temperature for 2 hours to obtain silica-coated Xuan paper. 6) Dissolve 0.5 g of beeswax in 20 g of anhydrous ethanol, heat at 65℃ for 30 min until the system is completely clear, and then spray it onto the surface of the silica-coated Xuan paper obtained in step 5). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 48 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating Xuan paper with a bird's nest-rice leaf composite structure.
[0051] Figure 1 The silica nanoparticles prepared in this embodiment have a near-spherical morphology and a diameter of approximately 64 nm. Figure 2 This is a surface morphology diagram of Xuan paper. As can be seen from the diagram, compared to the internal microstructure of Xuan paper, which features disordered fiber interweaving and abundant inter-fiber pores (such as...), the surface morphology of Xuan paper is significantly different. Figure 2 As shown in the figure, the surface morphology of Xuan paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure prepared in this embodiment is as follows. Figure 3As shown, polydimethylsiloxane acts as a stable bonding layer. High aspect ratio silane coupling agent-modified cellulose nanofibers form a continuous network framework through good interfacial compatibility and physical entanglement. Silica nanoparticles are mechanically interlocked on the silane coupling agent-modified cellulose nanofibers, imparting nanoscale roughness. Beeswax reduces surface energy. The interaction of these four components endows the Xuan paper with superhydrophobicity, with a water contact angle of 153.6° (e.g., ...). Figure 4 As shown), compared to the original Xuan paper's 68.9° (as shown), Figure 5 (As shown) increased by 122.9%.
[0052] Figure 6 A photograph of the original Xuan paper. Figure 7 The image shows a photograph of Xuan paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure, prepared in Example 1 of this invention. As shown in the image, the light transmittance of the Xuan paper modified with this coating is 43.9%, higher than the original Xuan paper's 34.8%. A photograph of the paper before coating is also shown (e.g., [image of the original paper]). Figure 6 As shown in the image, the SUST logo is clearly visible. (See the photo after painting.) Figure 7 As shown, the "SUST" lettering is clearly visible, directly confirming the transparency of the prepared coating. The coating color difference ΔE is 2.10, which is below the visual resolution threshold of 5, proving that the coating has excellent transparency and does not change the original appearance and color of the Xuan paper.
[0053] After sandpaper abrasion, tape peeling, and finger rubbing tests, the water contact angles of the coated Xuan paper were 150.8°, 150.3°, and 150.6°, respectively, and it still maintained superhydrophobicity, proving that the coating has excellent mechanical durability.
[0054] After soaking for 12 hours at pH values of 5 and 10, the water contact angle of the coated Xuan paper was 151.0° and 149.8°, respectively, proving that the coating has excellent resistance to acid and alkali corrosion.
[0055] The tensile strength of the coated Xuan paper is 25.0 MPa, which is 58.2% higher than that of the original Xuan paper.
[0056] Example 2 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 5% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 5 g of methyltrimethoxysilane dropwise. The mass ratio of methyltrimethoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 1:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 8000 rpm for 5 min, the silane coupling agent modified cellulose nanofiber is obtained after washing 3 times with anhydrous ethanol. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 500 rpm for 12 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 8000 rpm and dried at 80℃ for 6 h to prepare silica nanoparticles. 3) Mix polydimethylsiloxane, curing agent and tetrahydrofuran at a mass ratio of 1:0.1:10, and then spray it onto the surface of Xuan paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times. Each spraying time is 3 s. Pre-cur at room temperature for 2 h to obtain polydimethylsiloxane coated Xuan paper. 4) The silane coupling agent modified cellulose nanofibers prepared in step 1) are mixed with anhydrous ethanol at a mass ratio of 0.025:1. The mixture is then sprayed onto the surface of the polydimethylsiloxane-coated Xuan paper obtained in step 3). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 2 h to obtain Xuan paper with an imitation bird's nest structure middle layer coating. 5) Mix the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.025:1, and then spray the mixture onto the surface of the bird's nest structure intermediate layer coated paper obtained in step 4). Pre-cur at room temperature for 2 hours to obtain silica-coated Xuan paper. 6) Dissolve 0.25 g of beeswax in 20 g of anhydrous ethanol, heat at 65℃ for 30 min until the system is completely clear, and then spray it onto the surface of the silica-coated Xuan paper obtained in step 5). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 48 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating Xuan paper with a bird's nest-rice leaf composite structure.
[0057] Compared to the disordered interweaving of fibers and the rich pores between fibers in the microstructure of Xuan paper (such as... Figure 2 As shown in the figure, the surface morphology of Xuan paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure prepared in this embodiment is as follows. Figure 8As shown, polydimethylsiloxane acts as a stable bonding layer, and silane coupling agent modified cellulose nanofibers with high aspect ratio form a continuous network skeleton through good interfacial compatibility and physical entanglement. Silica nanoparticles are mechanically interlocked on silane coupling agent modified cellulose nanofibers, giving them nanoscale roughness. Beeswax reduces surface energy. The interaction of the four components gives Xuan paper superhydrophobicity, with a water contact angle of 152.6°, which is 121.5% higher than that of the original Xuan paper. The light transmittance of the Xuan paper treated with this coating is 59.1%, higher than the original Xuan paper's 34.8%, and the color difference ΔE is 1.88, lower than the visual resolution threshold of 5, proving that the coating has excellent transparency and does not change the original appearance and color of the Xuan paper. After sandpaper abrasion, tape peeling, and finger rubbing tests, the water contact angles of the coated Xuan paper are 150.2°, 150.8°, and 150.1°, respectively, still maintaining superhydrophobicity, proving that the coating has excellent mechanical durability. After soaking for 12 h at pH 5 and 10, the water contact angles of the coated Xuan paper are 150.5° and 150.8°, proving that the coating has excellent resistance to acid and alkali corrosion. The tensile strength of the coated Xuan paper is 24.9 MPa, which is 57.6% higher than that of the original Xuan paper.
[0058] Example 3 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 3% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 5 g of ethyltrimethoxysilane dropwise. The mass ratio of ethyltrimethoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 1:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 10000 rpm for 5 min, and washing with anhydrous ethanol 3 times, silane coupling agent modified cellulose nanofiber is obtained. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 1000 rpm for 12 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 10000 rpm and dried at 60℃ for 8 h to prepare silica nanoparticles. 3) Mix polydimethylsiloxane, curing agent and tetrahydrofuran at a mass ratio of 1:0.1:10, and then spray it onto the surface of Xuan paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times. Each spraying time is 3 s. Pre-cur at room temperature for 2 h to obtain polydimethylsiloxane coated Xuan paper. 4) The silane coupling agent modified cellulose nanofibers prepared in step 1) are mixed with anhydrous ethanol at a mass ratio of 0.0025:1. The mixture is then sprayed onto the surface of the polydimethylsiloxane-coated Xuan paper obtained in step 3). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 2 h to obtain Xuan paper with an imitation bird's nest structure middle layer coating. 5) Mix the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.0025:1, and then spray the mixture onto the surface of the bird's nest structure intermediate layer coated paper obtained in step 4). Pre-cur at room temperature for 2 hours to obtain silica-coated Xuan paper. 6) Dissolve 0.25 g of carnauba wax in 20 g of anhydrous ethanol, heat at 86℃ for 30 min until the system is completely clear, and then spray it onto the surface of the silica-coated Xuan paper obtained in step 5). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 48 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating Xuan paper with a bird's nest-rice leaf composite structure.
[0059] The water contact angle of Xuan paper treated with the fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure prepared in this embodiment is 153.8°, an increase of 123.2% compared to the original Xuan paper, exhibiting superhydrophobic properties. The light transmittance of the Xuan paper modified with this coating is 53.2%, higher than the 34.8% of the original Xuan paper, and the color difference ΔE is 1.78, lower than the visual resolution threshold of 5, proving that the coating has excellent transparency and does not change the original appearance and color of the Xuan paper. After sandpaper abrasion, tape peeling, and finger rubbing tests, the water contact angles of the Xuan paper treated with this coating are 147.5°, 147.6°, and 148.7°, respectively, still exhibiting high hydrophobicity, proving that the coating has excellent mechanical durability. After soaking for 12 h at pH 5 and 10, the water contact angles of the Xuan paper treated with this coating are 150.6° and 150.5°, proving that the coating has excellent resistance to acid and alkali corrosion. The tensile strength of the Xuan paper treated with this coating is 23.7. MPa, which is 50% higher than that of the original Xuan paper.
[0060] Example 4 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 3% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 10 g of propyltrimethoxysilane dropwise. The mass ratio of propyltrimethoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 2:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 9000 rpm for 5 min, and washing with anhydrous ethanol 3 times, silane coupling agent modified cellulose nanofiber is obtained. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 9000 rpm for 12 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 10000 rpm and dried at 80℃ for 4 h to prepare silica nanoparticles. 3) Mix polydimethylsiloxane, curing agent and tetrahydrofuran at a mass ratio of 1:0.1:10, and then spray it onto the surface of Xuan paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times. Each spraying time is 3 s. Pre-cur at room temperature for 2 h to obtain polydimethylsiloxane coated Xuan paper. 4) The silane coupling agent modified cellulose nanofibers prepared in step 1) are mixed with anhydrous ethanol at a mass ratio of 0.025:1. The mixture is then sprayed onto the surface of the polydimethylsiloxane-coated Xuan paper obtained in step 3). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 2 h to obtain Xuan paper with an imitation bird's nest structure middle layer coating. 5) Mix the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.025:1, and then spray the mixture onto the surface of the bird's nest structure intermediate layer coated paper obtained in step 4). Pre-cur at room temperature for 2 hours to obtain silica-coated Xuan paper. 6) Dissolve 0.5 g of candle wax in 20 g of anhydrous ethanol, heat at 73℃ for 30 min until the system is completely clear, and then spray it onto the surface of the silica-coated Xuan paper obtained in step 5). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 48 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating Xuan paper with a bird's nest-rice leaf composite structure.
[0061] The water contact angle of Xuan paper treated with the fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure prepared in this embodiment is 151.7°, an increase of 120.2% compared to the original Xuan paper, exhibiting superhydrophobic properties. The light transmittance of the Xuan paper modified with this coating is 56.5%, higher than the 34.8% of the original Xuan paper, and the color difference ΔE is 2.20, lower than the visual resolution threshold of 5, proving that the coating has excellent transparency and does not change the original appearance and color of the Xuan paper. After sandpaper abrasion, tape peeling, and finger rubbing tests, the water contact angles of the Xuan paper treated with this coating are 144.7°, 146.9°, and 147.7°, respectively, still exhibiting high hydrophobicity, proving that the coating has excellent mechanical durability. After soaking for 12 h at pH 5 and 10, the water contact angles of the Xuan paper treated with this coating are 149.1° and 150.3°, proving that the coating has excellent resistance to acid and alkali corrosion. The tensile strength of the Xuan paper treated with this coating is 24.3. MPa, which is 53.8% higher than that of the original Xuan paper.
[0062] Example 5 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 1% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 7.5 g of n-hexyltrimethoxysilane dropwise. The mass ratio of n-hexyltrimethoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 1.5:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 9000 rpm for 5 min, the silane coupling agent modified cellulose nanofiber is obtained by washing three times with anhydrous ethanol. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 9000 rpm for 24 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 9000 rpm and dried at 60℃ for 6 h to prepare silica nanoparticles. 3) Mix polydimethylsiloxane, curing agent and tetrahydrofuran at a mass ratio of 1:0.1:20 and spray it onto the surface of printing paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 15 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. Pre-cur at room temperature for 4 h to obtain polydimethylsiloxane coated printing paper. 4) The silane coupling agent modified cellulose nanofibers prepared in step 1) are mixed with anhydrous ethanol at a mass ratio of 0.010:1. The mixture is then sprayed onto the surface of the polydimethylsiloxane coated printing paper obtained in step 3). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 15 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 4 h to obtain the bird's nest structure intermediate layer coated printing paper. 5) Mix the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.010:1, and then spray the mixture onto the surface of the bird's nest structure intermediate layer coating printing paper obtained in step 4). Pre-cur at room temperature for 4 h to obtain silica-coated printing paper. 6) Dissolve 0.3 g of rice bran wax in 20 g of anhydrous ethanol, heat at 80℃ for 30 min until the system is completely clear, and then spray it onto the surface of the silica-coated printing paper obtained in step 5). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 15 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 24 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating printing paper with a bird's nest-rice leaf composite structure.
[0063] Example 6 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 1% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 5 g of octyltrimethoxysilane dropwise. The mass ratio of octyltrimethoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 1:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 8000 rpm for 5 min, and washing with anhydrous ethanol 3 times, silane coupling agent modified cellulose nanofiber is obtained. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 800 rpm for 12 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 8000 rpm and dried at 80℃ for 5 h to prepare silica nanoparticles. 3) Mix polydimethylsiloxane, curing agent and tetrahydrofuran in a mass ratio of 1:0.1:5 and spray it onto the surface of printing paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 10 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. Pre-cur at room temperature for 3 h to obtain polydimethylsiloxane coated printing paper. 4) The silane coupling agent modified cellulose nanofibers prepared in step 1) are mixed with anhydrous ethanol at a mass ratio of 0.01:1. The mixture is then sprayed onto the surface of the polydimethylsiloxane coated printing paper obtained in step 3). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 10 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 3 h to obtain a bird's nest-like structure intermediate layer coated printing paper. 5) Mix the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.01:1, and then spray the mixture onto the surface of the bird's nest structure intermediate layer coated paper obtained in step 4). Pre-cur at room temperature for 3 h to obtain silica-coated printing paper. 6) Dissolve 0.4 g of beeswax in 20 g of anhydrous ethanol, heat at 65℃ for 30 min until the system is completely clear, and then spray it onto the surface of the silica-coated printing paper obtained in step 5). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 10 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 24 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating printing paper with a bird's nest-rice leaf composite structure.
[0064] Example 7 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 1% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 10 g of decyltrimethoxysilane dropwise. The mass ratio of decyltrimethoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 2:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 8500 rpm for 5 min, and washing with anhydrous ethanol 3 times, silane coupling agent modified cellulose nanofiber is obtained. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 1000 rpm for 18 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 8500 rpm and dried at 60℃ for 8 h to prepare silica nanoparticles. 3) Mix polydimethylsiloxane, curing agent and tetrahydrofuran at a mass ratio of 1:0.1:15, and then spray it onto the surface of Xuan paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 10 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times. Each spraying time is 3 s. Pre-cur at room temperature for 2 h to obtain polydimethylsiloxane coated Xuan paper. 4) After uniformly mixing the silane coupling agent modified cellulose nanofibers prepared in step 1) with anhydrous ethanol at a mass ratio of 0.02:1, the mixture is sprayed onto the surface of the polydimethylsiloxane coated Xuan paper obtained in step 3). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 10 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is pre-cured at room temperature for 2 h to obtain Xuan paper with an imitation bird's nest structure middle layer coating. 5) Mix the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.02:1, and then spray the mixture onto the surface of the bird's nest structure intermediate layer coated paper obtained in step 4). Pre-cur at room temperature for 2 hours to obtain silica-coated Xuan paper. 6) Dissolve 0.3 g of beeswax in 20 g of anhydrous ethanol, heat at 65℃ for 30 min until the system is completely clear, and then spray it onto the silica-coated Xuan paper obtained in step 5). The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 10 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 48 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating Xuan paper with a bird's nest-rice leaf composite structure.
[0065] Example 8 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 5% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 7.5 g of methyltriethoxysilane dropwise. The mass ratio of methyltriethoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 1.5:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 9500 rpm for 5 min, the silane coupling agent modified cellulose nanofiber is obtained by washing three times with anhydrous ethanol. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 900 rpm for 24 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 9500 rpm and dried at 60℃ for 4 h to prepare silica nanoparticles. 3) After mixing polydimethylsiloxane, curing agent and tetrahydrofuran at a mass ratio of 1:0.1:20, the mixture is sprayed onto the surface of kraft paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 15 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 4 h to obtain polydimethylsiloxane coated kraft paper. 4) The silane coupling agent modified cellulose nanofibers prepared in step 1) are mixed with anhydrous ethanol at a mass ratio of 0.005:1. The mixture is then sprayed onto the surface of the polydimethylsiloxane-coated kraft paper obtained in step 3). The spray gun nozzle diameter is 0.5 mm, the spraying distance is 15 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 4 h to obtain the kraft paper with the middle layer imitating the bird's nest structure. 5) After uniformly mixing the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.005:1, spray it onto the surface of the bird's nest structure intermediate layer coated paper obtained in step 4), and pre-cur it at room temperature for 4 h to obtain silica-coated kraft paper. 6) Dissolve 0.4 g of beeswax in 20 g of anhydrous ethanol, heat at 65℃ for 30 min until the system is completely clear, and then spray it onto the silica-coated kraft paper obtained in step 5). The spray gun nozzle diameter is 0.5 mm, the spraying distance is 15 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 24 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating on kraft paper with a bird's nest-rice leaf composite structure.
[0066] Example 9 This embodiment provides a method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure, specifically including the following steps: 1) Mix 5 ml of cellulose nanofiber aqueous dispersion with 5% solid content with 45 ml of anhydrous ethanol thoroughly. Adjust the pH of the system to 4 with glacial acetic acid. Then add 5 g of methyltriisopropoxysilane dropwise. The mass ratio of methyltriisopropoxysilane to cellulose nanofiber aqueous dispersion and anhydrous ethanol is 1:8. The grafting modification is completed by reacting at 60℃ for 3 h. After centrifugation at 10000 rpm for 5 min, and washing with anhydrous ethanol 3 times, silane coupling agent modified cellulose nanofiber is obtained. 2) Tetraethyl orthosilicate, anhydrous ethanol and ammonia were mixed in a volume ratio of 5:25:1 and stirred magnetically at 800 rpm for 12 h at room temperature. After the reaction was completed, the precipitate was separated by centrifugation at 10000 rpm and dried at 60℃ for 7 h to prepare silica nanoparticles. 3) After mixing polydimethylsiloxane, curing agent and tetrahydrofuran in a mass ratio of 1:0.1:5, spray it onto the surface of kraft paper. The nozzle diameter of the spray gun is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is pre-cured at room temperature for 3 h to obtain polydimethylsiloxane coated kraft paper. 4) The silane coupling agent modified cellulose nanofibers prepared in step 1) are mixed with anhydrous ethanol at a mass ratio of 0.015:1. The mixture is then sprayed onto the surface of the polydimethylsiloxane-coated kraft paper obtained in step 3). The spray gun nozzle diameter is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the mixture is sprayed 3 times, with each spraying time being 3 s. The mixture is then pre-cured at room temperature for 3 h to obtain the kraft paper with the middle layer imitating the bird's nest structure. 5) Mix the silica nanoparticles prepared in step 2) with anhydrous ethanol at a mass ratio of 0.015:1, and then spray the mixture onto the surface of the bird's nest structure intermediate layer coated paper obtained in step 4). Pre-cur at room temperature for 3 h to obtain silica-coated kraft paper. 6) Dissolve 0.3 g of carnauba wax in 20 g of anhydrous ethanol, heat at 86℃ for 30 min until the system is completely clear, and then spray it onto the silica-coated kraft paper obtained in step 5). The spray gun nozzle diameter is 0.5 mm, the spraying distance is 20 cm, the spraying pressure is 0.2 MPa, and the spraying is done 3 times, with each spraying time being 3 s. The paper is cured at room temperature for 24 h to obtain a fluorine-free, high-strength, multifunctional superhydrophobic coating on kraft paper with a bird's nest-rice leaf composite structure.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating featuring a bird's nest-rice leaf composite structure, characterized in that, Includes the following steps: S1: After mixing polydimethylsiloxane, curing agent and tetrahydrofuran evenly, spray it onto the paper surface and perform a room temperature pre-curing to obtain polydimethylsiloxane coated paper. S2: After uniformly mixing silane coupling agent modified cellulose nanofibers with anhydrous ethanol, the mixture is sprayed onto the surface of the polydimethylsiloxane coated paper and pre-cured at room temperature for a second time to obtain paper coated with a bird's nest-like structure intermediate layer. S3: After uniformly mixing silica nanoparticles with tetrahydrofuran, spray the mixture onto the surface of the paper coated with the bird's nest structure intermediate layer, and perform three room temperature pre-curing processes to obtain silica-coated paper. S4: Dissolve the wax in anhydrous ethanol, heat at a constant temperature until the system is completely clear, then spray it onto the surface of silica-coated paper and cure at room temperature to obtain the paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating with a bird's nest-rice leaf composite structure.
2. The method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic paper coated with a bird's nest-rice leaf composite structure according to claim 1, characterized in that, The mass ratio of polydimethylsiloxane, curing agent and tetrahydrofuran is 1:0.1:(5~20); the time for the first room temperature pre-curing is 2~4 h.
3. The method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic paper coated with a bird's nest-rice leaf composite structure according to claim 1, characterized in that, The preparation process of the silane coupling agent modified cellulose nanofibers is as follows: the aqueous dispersion of cellulose nanofibers is mixed evenly with anhydrous ethanol, the pH value of the system is adjusted to 4 with glacial acetic acid, and then the silane coupling agent is added dropwise. After constant temperature reaction, the silane coupling agent modified cellulose nanofibers are obtained. The silane coupling agent includes one of methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, n-hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, methyltriethoxysilane, and methyltriisopropoxysilane.
4. The method for preparing a paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating of a bird's nest-rice leaf composite structure according to claim 3, characterized in that, The solid content of the cellulose nanofiber aqueous dispersion is 1%~5%; the mass ratio of the silane coupling agent to the cellulose nanofiber aqueous dispersion and anhydrous ethanol is (1~2):8; the volume ratio of the cellulose nanofiber aqueous dispersion to anhydrous ethanol is 1:
9.
5. The method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic paper coated with a bird's nest-rice leaf composite structure according to claim 1, characterized in that, The mass ratio of the silane coupling agent-modified cellulose nanofibers to anhydrous ethanol is (0.0025~0.025):1; the secondary room temperature pre-curing time is 2~4 h.
6. The method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic paper coated with a bird's nest-rice leaf composite structure according to claim 1, characterized in that, The mass ratio of silica nanoparticles to tetrahydrofuran is (0.0025~0.025):1, and the amount of silica nanoparticles added is equal to the content of silane coupling agent modified cellulose nanofibers; the time for the three room temperature pre-curing is 2~4 h.
7. A method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic paper coated with a bird's nest-rice leaf composite structure according to claim 1, characterized in that, The preparation process of the silica nanoparticles is as follows: tetraethyl orthosilicate, anhydrous ethanol and ammonia water are mixed in a volume ratio of 5:25:1, and the mixture is magnetically stirred at 500~1000 rpm at room temperature for 12~24 h. After the reaction is completed, the precipitate is separated by centrifugation at 8000~10000 rpm, and the precipitate is dried at 60~80℃ for 4~8 h.
8. A method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic paper coated with a bird's nest-rice leaf composite structure according to claim 1, characterized in that, In step S4, 0.25~0.5 g of wax is dissolved in 20 g of anhydrous ethanol; the curing time at room temperature is 24~48 h; the wax includes one of beeswax, carnauba wax, candle wax, rice bran wax and insect wax.
9. A method for preparing a fluorine-free, high-strength, multifunctional superhydrophobic paper coated with a bird's nest-rice leaf composite structure according to claim 1, characterized in that, The spraying process in steps S1 to S4 is as follows: spray gun nozzle diameter 0.5 mm, spraying distance 10~20 cm, spraying pressure 0.2 MPa; each layer is sprayed 3 times, and the single spraying time is 3 s.
10. A type of paper coated with a fluorine-free, high-strength, multifunctional superhydrophobic coating featuring a bird's nest-rice leaf composite structure, characterized in that... It is prepared by the method described in any one of claims 1 to 9.